Prediction of Risk Factors for Economic Status and Anemia with Chronic Energy Deficiency in Pregnant Women in the Tamalate Community Health Center Area, Makassar City - Marhaeni; Apriani; Wirawati Amin; Hastuti Husain (Afiyatun Journal of Health Sciences, 2026)
Background: Chronic energy deficiency (CED) affects 35–75% of pregnant women globally, with the highest prevalence occurring in the third trimester of pregnancy. National prevalence in Indonesia stands at 16.9%, with 12.1% in Makassar City and 19.38% at Tamalate Community Health Center. Multiple factors—including poverty, prenatal nutrition deficiency, anemia, and limited knowledge—accumulate in behaviors that negatively impact child stunting outcomes. Methods: A quantitative observational analytical study using a case-control design was conducted on 140 subjects at Puskesmas Tamalate, Makassar, comprising 70 CED cases and 70 non-CED controls selected by simple random sampling. Economic status was assessed by monthly family income level, and anemia status was determined by hemoglobin (Hb) measurement. Data were processed and analyzed using the Odds Ratio (OR) statistical test with SPSS version 24. Results: Economic status was significantly associated with CED in pregnant women (p=0.000 < α=0.05), with a predicted OR of 5.54 (95% CI: 2.67–11.47). Anemia status was also significantly associated with CED (p=0.000 < α=0.05), with a predicted OR of 9.7 (95% CI: 3.5–27.2). Conclusion: Low family income and anemia are significant risk factors for CED in pregnant women. Adequate nutritional education utilizing affordable food sources and Hb screening before and during pregnancy are strongly recommended to reduce CED incidence.